Symbol Digit Modalities Test: Greek Normative Data for the Oral and Written Version and Discriminative Validity in Patients with Multiple Sclerosis. (8th May 2020) - Messinis, Lambros; Bakirtzis, Christos; Kosmidis, Mary Helen; Economou, Alexandra; Nasios, Grigorios; Anyfantis, Emmanouil; Konitsiotis, Spiridon; Ntoskou, Aikaterini; Peristeri, Eleni; Dardiotis, Efthymios; Grigoriadis, Nikolaos; Gourzis, Phillipos; et al.
Abstract: Objectives: The purpose of this study was to generate normative data on the Symbol Digits Modalities Test (SDMT) for the written and oral versions in the Greek adult population. We also investigated the test's validity in discriminating the performance of healthy adults from two groups of adults diagnosed with relapsing remitting (RRMS) and secondary progressive (SPMS) multiple sclerosis. Method: The sample consisted of 609 healthy men and women between the ages of 18 and 65. All participants were monolingual native Greek adult speakers. Each healthy participant was administered either the written ( n  = 460) or oral ( n  = 149) versions of the SDMT. Discriminant validity was examined by comparing 35 healthy participants who had completed the oral version of the SDMT to 35 age - and education-matched RRMS and SPMS patients. Results: Linear regression models explained between 36% and 55% of the variance in the SDMT oral and written version scores. Age was the strongest predictor of difference in SDMT written and oral version performance, followed by education that also accounted for a further proportion of the SDMT variance. On the contrary, gender was found not to contribute significantly to the variance in the SDMT for either the written or the oral versions. As a result, age- and education-adjusted norms were generated. Regarding the tests discriminative validity, we found that both MS patient groups scored significantly lower than the healthy group. Conclusions: This is the first study to provide comprehensive normative data for the SDMT in the adult population in Greece, impacting the future practice of neuropsychological assessment in this country.